Vortex Motion Law of an Evolutionary Ginzburg-Landau Equation in 2 Dimensions (Journal of Partial Differential Equations, 2001)
We study the asymptotic behavior of solutions to an evolutionary Ginzburg-Landau equation. We also study the dynamical law of Ginzburg-Landau vortices of this equation under the Neuman boundary conditions. Away from the vortices, we use some measure theoretic arguments used by F.H.Lin in [1] to show the strong convergence of solutions. This is a continuation of our earlier work [2].